Inflation and Government Size in Iran: Threshold Regression Approach - Hassan Samanipour; Esmaiel Abounoori; Younes Nademi (پژوهشهای اقتصادی, 2016)
The main aim in this paper is to test the nonlinearity relationship between inflation and the government size in Iran during 1974-2012. To this end, we use a threshold regression approach and the Hansen nonlinearity test.  The result indicates nonlinear relationship between inflation and government size.  According to the results, an increase in government size by 0.22 will increase the rate of inflation with decreasing gradient, but afterwards any increase in government size will increase the rate of inflation.  In other words, under a small government regime, government size has negative effect on inflation, but in a large government regime, it has positive effect on inflation.